2002
DOI: 10.46989/001c.20313
|View full text |Cite
|
Sign up to set email alerts
|

Growth And Survival Of The White Leg Shrimp (Litopenaeus Vannamei) Reared Intensively In The Brackish Water Of The Israeli Negev Desert

Abstract: As from January 2010 The Israeli Journal of Aquaculture-Bamidgeh (IJA) will be published exclusively as an on-line Open Access (OA) quarterly accessible by all AquacultureHub (http://www.aquaculturehub.org) members and registered individuals and institutions. Please visit our website (http://siamb.org.il) for free registration form, further information and instructions. This transformation from a subscription printed version to an on-line OA journal, aims at supporting the concept that scientific peer-reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
(2 reference statements)
1
2
0
Order By: Relevance
“…These results are in agreement with Arambul‐Muñoz et al (2019), Gao et al (2017), Yu et al (2009) and Williams et al (1996). Similar observations have been reported for studies of L. vannamei and P. setiferus (Araneda et al, 2008; Williams et al, 1996) Consistent results have also observed similar patterns measuring different independent factors such as salinity and temperature (Appelbaum et al, 2002; Davis & Arnold, 1998; Roy et al, 2020; Samocha et al, 2004; Van Wyk et al, 1999; Williams et al, 1996).…”
Section: Discussionsupporting
confidence: 82%
“…These results are in agreement with Arambul‐Muñoz et al (2019), Gao et al (2017), Yu et al (2009) and Williams et al (1996). Similar observations have been reported for studies of L. vannamei and P. setiferus (Araneda et al, 2008; Williams et al, 1996) Consistent results have also observed similar patterns measuring different independent factors such as salinity and temperature (Appelbaum et al, 2002; Davis & Arnold, 1998; Roy et al, 2020; Samocha et al, 2004; Van Wyk et al, 1999; Williams et al, 1996).…”
Section: Discussionsupporting
confidence: 82%
“…This result can be explained by density effects on survival, as in our study, shrimps were cultured at a lower density than the rearing density in previous work (Amaya et al, 2007). Indeed, previous studies have shown that the culturing density of L. vannamei negatively correlates with survival (Appelbaum et al, 2002). Moreover, survival might be affected by lower main ion concentrations such as potassium, which was not the case in our study.…”
Section: The Survival and Yield Of Pl-55contrasting
confidence: 67%
“…Electrodialysis experiments were performed with a mixed solution of 1000 ppm Na + (as Na 2 SO 4 , ≥99% purity, Merck) and 100 ppm Mg 2+ (as MgSO 4 ·7H 2 O, ≥99.5% purity, Merck) dissolved in deionized water (18.2 MΩ cm)—concentrations that are similar to those found in the brackish water of the Israel Negev region. 32 ED was conducted at a constant current density of 2.5 mA cm −2 , applied using a Lion LE 305D DC laboratory power supplier. A single cell-pair was used in the following configuration (illustrated in Fig.…”
Section: Methodsmentioning
confidence: 99%